2019
DOI: 10.1186/s12903-019-0798-1
|View full text |Cite
|
Sign up to set email alerts
|

In vitro study of effects of aging and processing conditions on colour change in maxillofacial silicone elastomers

Abstract: Background The inherent colour change in maxillofacial silicone elastomers becomes perceptible 6–12 months after fabrication. Determining the factors that accelerate the degradation of the prosthesis can help the clinicians increase its life span. Therefore, the aim of the study was to investigate the effect of time passage, processing temperature, and molding-stone colour on the colour change of maxillofacial silicone elastomers after darkroom storage for 6000 h. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 39 publications
0
12
0
1
Order By: Relevance
“…[1][2][3]5,7,8,10,[13][14][15][16][17]22 According to Goiato et al 9 and Mancuso et al, 15 the use of 1,008 hours of accelerated aging (in vitro) corresponds to 1 year of constant use of a silicone prosthesis by the patient. 9,15 Therefore, if a silicone prosthesis generally has a maximum clinical durability of 1 year, 2,[4][5][6][7]10,13,15 aging for 1,008 hours (in vitro) is sufficient to simulate a clinical situation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[1][2][3]5,7,8,10,[13][14][15][16][17]22 According to Goiato et al 9 and Mancuso et al, 15 the use of 1,008 hours of accelerated aging (in vitro) corresponds to 1 year of constant use of a silicone prosthesis by the patient. 9,15 Therefore, if a silicone prosthesis generally has a maximum clinical durability of 1 year, 2,[4][5][6][7]10,13,15 aging for 1,008 hours (in vitro) is sufficient to simulate a clinical situation.…”
Section: Discussionmentioning
confidence: 99%
“…Facial defects are usually caused by cancer, traumatic accidents, or congenital diseases and can affect speech, quality of life, and the psychological state of an individual. 1 Maxillofacial prostheses can be used to mask these facial defects, 1 improve aesthetics, 2 3 4 5 6 7 8 9 quality of life, and self-esteem of the patients, 3 5 in addition to protecting areas that contain bloody tissues. 3 5 These prostheses also allow many patients with orofacial defects to return to their daily activities in public.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The main challenge in the performance of an ideal facial prosthesis is the degradation in appearance, either due to changes in color or deterioration of the physical properties. [1][2][3] A large number of people acquire facial defects, unfortunately, because of ablative surgery, trauma, and congenital deformity. Facial prosthesis should restore the normal function and anatomy, protect the tissues of the defect, and provide great benefits to the patients allowing improvement in selfesteem aiding the patient to lead as normal life as possible.…”
Section: Maxillofacial Prosthetics Has Developedmentioning
confidence: 99%
“…Cifter et al 36 investigated the effect of time passage, processing temperature, and molding-stone color on the color change of maxillofacial silicone elastomers, and they found that vulcanization temperature or the color of the molding stone has a significant effect on the color change over time. The molding-stone color and vulcanization temperature both affect the degree of color change after storage in a dark environment.…”
Section: Effect Of Nano Zinc Oxide Particles On Color Stability Of Famentioning
confidence: 99%